A case study of radioactive fallout - Reiter, Elmar R., author; Colorado State University, publisher (Colorado State University. Libraries, 1963)
During September 1961 a series of balloon ascents made from Flin Flon, Canada, carrying scintillation counters sensitive to gamma radiation, revealed the existence of shallow stable atmospheric layers carrying radioactive debris, presumably from the Russian test series during the same month. The debris layers encountered on September 14 and 15 have been studied in particular. The debris detected over Flin Flon on September 14, 2221 GCT, at 650 mb had undergone strong sinking motion. One may conclude that it came out of the stratosphere shortly prior to September 13, 12 GCT, entering the troposphere through the stable layer underneath the jet core, sometimes referred to as "jet-stream front". Beginning with September 17 a distinct area of radioactive fallout begins to appear at the surface over the eastern United States. Some of this debris seems to be identical with the one detected over Flin Flon, and it apparently was transported by the same jet stream. Part of the fallout is associated with a small collapsing cold dome travelling ahead of this jet stream.
CER63ERR7.
January 1963.
Prepared for the U.S. Navy Weather Research Facility, Norfork, Virginia.
Keywords: Radioactive fallout; Atmospheric radioactivity; Nuclear energy and meteorology